Funding liquidity and bank risk taking in commercial banks Malaysia - Oto, Suraidah (2019)
The aim of this paper is to examine the relationship between funding liquidity and bank risk taking in commercial banks Malaysia. To study funding liquidity and bank risk taking, lot of previous study was being reference in this study. Theories that were used in this study are the shift ability theory and the anticipated income theory. This study used three independent variable that been used by previous study. For the dependent variable, this study used loan loss provision. The result shows deposit has negative relationship toward loan loss provision. However, asset and loan shows the opposite result. This study used 8 local commercial banks Malaysia.